Buschke-Lowenstein tumour (BLT)/giant condyloma acuminatum (GCA): an immunopathogenesis insight - Paulus Mario Christopher; Hartono Kosim; Ratna Sari Wijaya; Silvi Suhardi; Linda Julianti Wijayadi (DiscoverSys Inc, 2020)
Buschke Lowenstein tumor (BLT)/giant condyloma acuminatum is a rare variant of a sexually transmitted infection caused by human papillomavirus (HPV) type 6 and 11. HPV has its viral factors that exist to avoid immune surveillance and control through 1) infecting only the basal layer of the epithelium, 2) downregulation of host immunity, 3) suppression of proinflammatory proteins essential for viral clearance. The incidence of BLT/GCA is estimated to be 0.1% in the general population, with males having 2.7 times increased risk than females. A BLT/GCA is characterized by verrucous tumor or palpable cauliflower-likemass, exophytic growth, flesh-colored, and uneven surface. The definitive diagnosis of BLT/GCA is typical morphology along with histopathological examination, and/or viral serotyping. Treatment of BLT/GCA requires a multidisciplinary approach, determined based on age, the extent of the lesion, organ involvement, and organ location.